Identification of GLPG/ABBV-2737, a Novel Class of Corrector, Which Exerts Functional Synergy With Other CFTR Modulators - de Wilde, Gert; Gees, Maarten; Musch, Sara; Verdonck, Katleen; Jans, Mia; Wesse, Anne-Sophie; Singh, Ashvani K.; Hwang, Tzyh-Chang; Christophe, Thierry; Pizzonero, Mathieu; Van der Plas, Steven; Desroy, Nicolas; et al. (Frontiers in Pharmacology, 2019)
The deletion of phenylalanine at position 508 (F508del) in cystic fibrosis transmembrane conductance regulator (CFTR) causes a severe defect in folding and trafficking of the chloride channel resulting in its absence at the plasma membrane of epithelial cells leading to cystic fibrosis. Progress in the understanding of the disease increased over the past decades and led to the awareness that combinations of mechanistically different CFTR modulators are required to obtain meaningful clinical benefit. Today, there remains an unmet need for identification and development of more effective CFTR modulator combinations to improve existing therapies for patients carrying the F508del mutation. Here, we describe the identification of a novel F508del corrector using functional assays. We provide experimental evidence that the clinical candidate GLPG/ABBV-2737 represents a novel class of corrector exerting activity both on its own and in combination with VX809 or GLPG/ABBV-2222.